Transcriptome and translatome changes in germinated pollen under heat stress uncover roles of transporter genes involved in pollen tube growth. (22nd December 2020) - Poidevin, Laetitia; Forment, Javier; Unal, Dilek; Ferrando, Alejandro
Abstract: Plant reproduction is one key biological process that is very sensitive to heat stress and, as a result, enhanced global warming becomes a serious threat to agriculture. In this work, we have studied the effects of heat on germinated pollen of Arabidopsis thaliana both at the transcriptional and translational level. We have used a high‐resolution ribosome profiling technology to provide a comprehensive study of the transcriptome and the translatome of germinated pollen at permissive and restrictive temperatures. We have found significant down‐regulation of key membrane transporters required for pollen tube growth by heat, thus uncovering heat‐sensitive targets. A subset of the heat‐repressed transporters showed coordinated up‐regulation with canonical heat‐shock genes at permissive conditions. We also found specific regulations at the translational level and we have uncovered the presence of ribosomes on sequences annotated as non‐coding. Our results demonstrate that heat impacts mostly on membrane transporters thus explaining the deleterious effects of heat stress on pollen growth. The specific regulations at the translational level and the presence of ribosomes on non‐coding RNAs highlights novel regulatory aspects on plant fertilization. Abstract : We have used Riboprofiling to study transcription and translation of pollen germinated under normal and heat stress conditions. We found specific translational adjustments and heat down‐regulation on transporter gene expression, providing molecular clues to the heat effects on plant fertilization